Azure Synapse Analytics cookbook : implement a limitless analytical platform using effective recipes for Azure Synapse /: implement a limitless analytical platform using effective recipes for Azure Synapse. (2022) - Agarwal, Gaurav; Muralidharan, Meenakshi; Srivathsa, Rohini
No abstract available